The Eclogues and Cynegetica of Nemesianus - Williams, Heather J. (Mnemosyne, Supplements, 1986)
Although editions of Nemesianus have been surprisingly numerous, very few have contributed appreciably to our understanding of this author, and most texts have been based on a very limited number of manuscripts. There has been no commentary of any length since that of Burman (1731) and there has never before been one in English covering the whole corpus. This book is an attempt to remedy those deficiencies. The text is the first to have been based on an examination of all the known manuscripts, and a detailed and accurate apparatus criticus is provided. The textual history of both poems is thoroughly discussed. The question of the authenticity of the Eclogues is examined and Nemesianus' authorship is held to be proved. The commentary is mainly concerned with textual and grammatical matters. There is also a bibliography.